The endarkenment - McDaniel, Jeffrey, 1967- (Pitt poetry series., 2008)
""Known for his commanding stage presence as a reader, McDaniel trades hard in his fourth book on his rough-and-tumble persona--a recovering addict from the working class streets--while also showing softer sides. McDaniel's sometimes awkward, if earnest searching might just be what allows him to find moments of great beauty, humor and stillness.""--Publishers Weekly "McDaniel is known for his talent performing his poems, however his voice doesn't lose its impact in written form. It may be more powerful because the reader can view the poet's unique ideas and phrases over and over until their